Dalla società plurale allo Stato delle masse Filosofia politica e sociologia in Emil Lederer (1882-1939) - Basso, Michele (Per la storia della filosofia politica, 2022)
This book represents the first monograph on the philosopher, economist and sociologist Emil Lederer (1882-1939). Director of the Archiv für Sozialwissenschaft und Sozialpolitik from 1922 to 1933, he was then forced to move to the United States to avoid persecution as a Jew (despite his conversion to Catholicism in 1908) and a socialist. There he became the Dean of the so-called 'University in Exile' at the New School for Social Research in New York. After sketching an updated picture of his intellectual biography and of the reception of his major works, the volume focuses on the issue of political order, and notably on the relationship between State and society. Before the outbreak of the First World War, Lederer was confident of being able to find a composition between State and the plurality of society, relying on the mediation skills of the middle classes. The First World War put in evidence certain contradictions of the modern liberal state that were intrinsic in its very origins; the State proves to be able to lose its connection with the structural plurality of society, becoming an abstract organisation, in Lederer's words rising definitively to the status of an 'abstract sovereignty'. This paves the way for the possibility of conceiving a political order no longer based on the connection between society and State, as in the liberal and constitutional tradition, but on a direct relationship between the leader and the masses. Such a relationship relies on the former's continuous ability to activate the emotions of the masses, and has no need for the internal reasoning typical of the dialectic between society and political institutions. According to Lederer, this will be the hallmark of the totalitarian State, analysed in his last, unfinished book, State of the masses (1939).